Reaching for the Sky : Empowering Girls Through Education - Sahni, Urvashi (Book collections on Project MUSE., 2017)
Since 2003 a privately funded high school in India has provided desperately needed education for girls from impoverished families in Lucknow, the capital and largest city in Uttar Pradesh. Urvashi Sahni, the founder of Prerna Girls School, has written a compelling narrative of how this modest school in northeast India has changed the lives of more than 5,000 girls and their families. Most important, it is through the perspectives of the girls themselves, rather than through a remote academic viewpoint, that Prerna's success unfolds. The book focuses on the importance of education in bringing about gender equality in a patriarchal society. It shows how girls learn to be equal and autonomous persons in school as part of their official curriculum and how they use this learning to transform their lives and those of their families. The book's central argument is that education can be truly transformative if it addresses the everyday reality of girls' lives and responds to their special needs and challenges with respect and care. The example of just one relatively small school in one corner of India, the message and the stories it tells will inspire anyone concerned about the necessity of girls' education, especially in developing countries. The lives of the girls at Prerna Girls School are largely representative of those of millions living in poor regions in countries where patriarchal structures and norms prevail.